Reprint of OASIS – Obesity Awareness and Insight Scale. Issue 4 (August 2018) - Gerretsen, Philip; Kim, Julia; Shah, Parita; Quilty, Lena; Balakumar, Thushanthi; Caravaggio, Fernando; Plitman, Eric; Chung, Jun Ku; Iwata, Yusuke; Pollock, Bruce G.; Dash, Satya; Sockalingam, Sanjeev; et al.
Abstract: Aims: Impaired illness awareness or not accepting that one has obesity is an understudied phenomenon that may negatively influence treatment adherence and clinical outcomes. The purpose of this study was to perform a systematic review of available measures of obesity awareness, and subsequently develop and validate a novel scale that measures the core domains of obesity awareness. Methods: A systematic review of the literature revealed no illness specific measure of subjective obesity awareness. As such, we designed the Obesity Awareness and Insight Scale (OASIS) to assess the following core domains of illness awareness: General Illness Awareness, Symptom Attribution, Awareness of Need for Treatment and the Negative Consequences attributable to the illness (www.illnessawarenessscales.com ). Participants (n = 100) were recruited from an online survey platform to assess the psychometric properties of OASIS. Results: The OASIS demonstrated strong internal consistency (Cronbach's alpha = 0.89), convergent ( r (98) = 0.65, p < 0.001) and discriminant validity, and test-retest reliability (intra-class correlation = 0.76). An exploratory factor analysis of OASIS revealed a single latent component. Conclusions: OASIS is an obesity-specific instrument that comprehensively measures subjective obesity awareness. OASIS can be used in epidemiological studies, intervention trials, and clinical practice to assess the impact of obesity awareness on treatment adherence and outcomes.